2015
DOI: 10.1017/s1751731115000397
|View full text |Cite
|
Sign up to set email alerts
|

SNPs detected in the yak MC4R gene and their association with growth traits

Abstract: MC4R (melanocortin 4 receptor) is expressed in the appetite-regulating areas of the brain and takes part in leptin signaling pathways. Sequencing of the coding region of the MC4R gene for 354 yaks identified the following five single nucleotide polymorphisms (SNPs): SNP1 (273C > T), SNP2 (321 G > T), SNP3 (864 C > A), SNP4 (1069G > C) and SNP5 (1206 G > C). SNP1, SNP2 and SNP3 were synonymous mutations, whereas SNP4 and SNP5 were missense mutations resulting in amino acid substitutions (V286L and R331S). Pairw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…The association analysis between the MC4R gene polymorphism with various body measurements and fat deposition traits was performed in 206 animals (Table 2). The overall results were concordant with previous studies in the coding region of the MC4R gene association reports [31,32,33,34]. The recent study in Hu sheep MC4R gene noted that similar to the polymorphisms in the coding region, variants in the regulatory regions are also exhibit a significant association with the body growth and meat quality traits of Hu sheep [35].…”
Section: Discussionsupporting
confidence: 89%
“…The association analysis between the MC4R gene polymorphism with various body measurements and fat deposition traits was performed in 206 animals (Table 2). The overall results were concordant with previous studies in the coding region of the MC4R gene association reports [31,32,33,34]. The recent study in Hu sheep MC4R gene noted that similar to the polymorphisms in the coding region, variants in the regulatory regions are also exhibit a significant association with the body growth and meat quality traits of Hu sheep [35].…”
Section: Discussionsupporting
confidence: 89%
“…For the MC4R gene, Cai et al (2015) reported that the haplotypes CGACG and CTCCC were associated with increased body weight and average daily gain in yaks. In this study, statistical analyses showed that in milk buffaloes, diplotype H1H2 was the most significantly associated with 305-day milk yield (P < 0.05), and individuals with diplotype H3H3 showed the highest protein percentage compared to the H1H1 and H1H2 haplotype combinations.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype of MC4R gene based on single nucleotide polymorphism has also been reported as genetic marker for body weight in female Beagle dogs (Zheng et al, 2014), sexual desire behavior, feed intake and finishing weight in rabbit (Fontanesi et al, 2013;El-Sabrout, 2017;El-Sabrout and Soliman, 2017), egg production in Langsan chicken (Yan et al, 2013), feed intake, body weight and ADG in yak (Cai et al, 2015), back fat thickness and marbling score in Korean cattle (Seong et al, 2012), birth body length in Kebumen cattle (Maharani et al, 2018), ADG, loin-eye area and meat quality in sheep (Zou et al, 2014) and milk production in buffalo (Deng et al, 2016). In the previous study, genetics analysis (SNPs detection, amino acid change, restriction enzyme mapping and phylogenetic tree) of MC4R gene were reported in Bligon goat (Latifah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%